A long term study (1938–2004) of arrival dates of migratory birds in middle Värmland - Borgström, Erik; Schütt, Lars (Ornis Svecica, 2006)
We present first spring arrival dates of 64 bird species in Råda, Sweden (60°00'N, 13°36'E) for the period 1938–2004 with almost all species covered more than 50 years. The trend was toward earlier dates in 60 species. The trend was strongest (average c. 20 days for the whole period) among water birds; their arrival was influenced by the breaking up of the ice of lake Råda. Land birds that winter within Europe shifted their arrival with on average c. 15 days earlier. Tropical migrants tended to show moderate or little change of dates (average c. 8 days). The Osprey Pandion haliaetus, being both a tropical migrant and a water bird, showed an advancement of 20 days, more than any other tropical migrant. The Crane Grus grus had a unique pattern. There was no advancement of arrival date in 1938–1988 (median 13 April), but it suddenly shifted to 27 March in 1989–2004.